A water-based zinc-iodine battery without ion exchange membrane and a preparation method thereof
Patent Information
- Application Number
- CN202310998071.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-08-09
AI Technical Summary
[0004]本发明的目的在于提供一种不含离子交换膜的水系锌-碘电池及制备方法,旨在解决现有的电池的制备方法的成本高的问题
[0026] This invention discloses a method for preparing an aqueous zinc-iodine battery without an ion exchange membrane. The method involves weighing a selenium source, sodium acetate, and an organic alcohol in a specific molar ratio, adding deionized water, and stirring to dissolve them to obtain a reaction solution. A cleaned zinc sheet is then immersed in the reaction solution to deposit the reaction. The reacted zinc sheet is then washed sequentially with deionized water and anhydrous ethanol, and vacuum dried to obtain a zinc negative electrode with an amorphous Se nanofilm on its surface, denoted as Zn@Se. Using Zn@Se as the negative electrode, an activated carbon coating or a self-supporting membrane as the positive electrode, and an aqueous solution containing zinc sulfate, zinc iodide, zinc bromide, and elemental iodine as the electrolyte, a zinc-iodine rechargeable battery is constructed. This invention provides a method for forming an amorphous Se film on the surface of a zinc sheet using a solution reaction method. The selenium to zinc ratio in this film decreases with increasing film thickness; as the film thickness increases from 1 micrometer to 10 micrometers, the Se:Zn molar ratio decreases from approximately 1:6 to 1:12. This amorphous Se film allows zinc ions to pass through. During charge-discharge cycles, a layer of amorphous Zn(OH)₂ and ZnO mixed nanosheet network structure is induced to grow through parasitic reactions, which suppresses hydrogen evolution, inhibits the shuttle effect of iodine ions, and improves the cycle life of the battery. The production process of this invention is extremely simple, requiring only the reaction of commercially available metallic Zn sheets in a reaction solution for a certain period of time. The raw materials used in this invention are widely available and inexpensive, resulting in low production costs and suitability for large-scale production. Batteries using the modified zinc anode of this invention exhibit excellent performance, operating stably for 30,000 cycles without short circuits. This invention solves the problem of the shuttle effect of polyiodine anions in existing aqueous zinc-iodine batteries.
Smart Images

Figure CN117013103B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrochemical energy storage device technology, and in particular to an aqueous zinc-iodine battery without an ion exchange membrane and its preparation method. Background Technology
[0002] With increasing demand for fossil fuels and worsening environmental pollution, developing high-performance, clean energy storage devices is an urgent task. Lithium-ion batteries are currently the dominant rechargeable batteries on the market, but lithium resources are limited, battery manufacturing costs are high, and the organic electrolytes used pose a fire and explosion risk. Therefore, developing low-cost, safe, and efficient new rechargeable battery systems is of practical significance, especially for large-scale energy storage systems. Zinc has a potential of -0.76V relative to the standard hydrogen electrode and a relatively large theoretical specific capacity of 820 mAh / g. Flow batteries can be constructed using zinc anodes and iodine-containing electrolytes (CN201410776231), but this type of battery requires an ion exchange membrane to separate the two different electrolytes, as well as an additional circulating water pump. Without an ion exchange membrane, due to the triiodine anion (I3), - The "shuttle effect" of the zinc anode causes it to react with the zinc anode, making the zinc anode prone to corrosion, gradually reducing the battery capacity and coulombic efficiency.
[0003] To suppress the shuttle effect of iodine, existing improved methods include: anchoring I2 on a porous support and investigating the effect of I2 loading on battery performance (Journal of Materials Chemistry A 2020, 8(7), 3785-3794); researchers have also used Nafion membranes to suppress the shuttle effect in zinc-iodine batteries (Energy & Environmental Science 2017, 10(3), 735-741); and constructing a Zn-BTC-like MOF layer on the zinc anode surface to selectively shield I3. - Ions, thereby suppressing the shuttle effect (Advanced Materials 2020, 32(38), 2004240). However, the preparation steps of these material coatings are complicated, it is not easy to process both sides of zinc at the same time, and the raw material cost is high, which will significantly reduce the cost advantage of zinc-iodine batteries. Summary of the Invention
[0004] The purpose of this invention is to provide an aqueous zinc-iodine battery without an ion exchange membrane and its preparation method, aiming to solve the problem of high cost in existing battery preparation methods.
[0005] To achieve the above objectives, in a first aspect, the present invention provides a surface-modified zinc anode for aqueous zinc-iodine batteries, the preparation method comprising the following steps:
[0006] Weigh out the selenium source, sodium acetate, and organic alcohol according to a certain molar ratio, add deionized water and stir to dissolve to obtain a reaction solution;
[0007] The cleaned zinc sheet is immersed in the reaction solution for deposition reaction. The zinc sheet after reaction is washed with deionized water and anhydrous ethanol in sequence. After vacuum drying, a zinc anode with an amorphous Se nanofilm on the surface is obtained, denoted as Zn@Se.
[0008] A zinc-iodine rechargeable battery is constructed by using Zn@Se as the negative electrode, an activated carbon coating or a self-supporting film as the positive electrode, and an aqueous solution containing zinc sulfate, zinc iodide, zinc bromide and elemental iodine as the electrolyte.
[0009] The selenium source is one or more of selenium dioxide, selenite, sodium selenite, and sodium biselenite, and sodium acetate is added to adjust the pH to 4.5-5.5;
[0010] Organic alcohols are one or more of ethanol, ethylene glycol, isopropanol, and glycerol.
[0011] The concentration of selenium in the selenium source is 0.1 - 0.5 M;
[0012] The concentration of the sodium acetate is 0.02 - 0.05 M;
[0013] The volume fraction of the organic alcohol is 5% - 30%.
[0014] The soaking is carried out at room temperature and normal pressure, and the soaking time is 1-12 hours;
[0015] The cleaning process includes ultrasonic cleaning of the zinc sheet with an organic solvent, rinsing with deionized water, and then drying.
[0016] The deposition reaction takes 0.5 to 2 hours.
[0017] The organic solvent is a mixture of acetone and ethanol.
[0018] The method for preparing the activated carbon coating includes:
[0019] Conductive carbon cloth or carbon paper is ultrasonically cleaned in 1 M dilute nitric acid for 3 hours, and then repeatedly cleaned with deionized water until neutral; after drying in an oven at 60°C for 6 hours, hydrophilic carbon cloth or hydrophilic carbon paper is obtained.
[0020] Porous activated carbon powder, polyvinylidene fluoride, and acetylene black were dispersed in N-methylpyrrolidone at a mass ratio of 8:1:1, and then magnetically stirred for 12 hours to obtain a carbon powder slurry with a concentration of 20 mg / mL.
[0021] The carbon powder slurry is uniformly coated onto the hydrophilic carbon cloth or hydrophilic carbon paper, and then dried in an oven at 100 °C for 12 hours to obtain an activated carbon coating.
[0022] Secondly, the present invention provides an aqueous zinc-iodine battery without an ion exchange membrane, comprising a negative electrode, a positive electrode, and an electrolyte;
[0023] The negative electrode is Zn@Se;
[0024] The positive electrode is an activated carbon coating or a self-supporting membrane;
[0025] The electrolyte is an aqueous solution containing zinc sulfate, zinc iodide, zinc bromide and elemental iodine.
[0026] This invention discloses a method for preparing an aqueous zinc-iodine battery without an ion exchange membrane. The method involves weighing a selenium source, sodium acetate, and an organic alcohol in a specific molar ratio, adding deionized water, and stirring to dissolve them to obtain a reaction solution. A cleaned zinc sheet is then immersed in the reaction solution to deposit the reaction. The reacted zinc sheet is then washed sequentially with deionized water and anhydrous ethanol, and vacuum dried to obtain a zinc negative electrode with an amorphous Se nanofilm on its surface, denoted as Zn@Se. Using Zn@Se as the negative electrode, an activated carbon coating or a self-supporting membrane as the positive electrode, and an aqueous solution containing zinc sulfate, zinc iodide, zinc bromide, and elemental iodine as the electrolyte, a zinc-iodine rechargeable battery is constructed. This invention provides a method for forming an amorphous Se film on the surface of a zinc sheet using a solution reaction method. The selenium to zinc ratio in this film decreases with increasing film thickness; as the film thickness increases from 1 micrometer to 10 micrometers, the Se:Zn molar ratio decreases from approximately 1:6 to 1:12. This amorphous Se film allows zinc ions to pass through. During charge-discharge cycles, a layer of amorphous Zn(OH)₂ and ZnO mixed nanosheet network structure is induced to grow through parasitic reactions, which suppresses hydrogen evolution, inhibits the shuttle effect of iodine ions, and improves the cycle life of the battery. The production process of this invention is extremely simple, requiring only the reaction of commercially available metallic Zn sheets in a reaction solution for a certain period of time. The raw materials used in this invention are widely available and inexpensive, resulting in low production costs and suitability for large-scale production. Batteries using the modified zinc anode of this invention exhibit excellent performance, operating stably for 30,000 cycles without short circuits. This invention solves the problem of the shuttle effect of polyiodine anions in existing aqueous zinc-iodine batteries. Attached Figure Description
[0027] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0028] Figure 1 The images show (a) an optical photograph and (b) a scanning electron microscope image of the zinc sheet after a brown amorphous Se nanofilm has been formed on its surface.
[0029] Figure 2 The results are: (a) XPS full spectrum after Se film is formed on the surface of zinc sheet negative electrode; (b) XRD spectrum comparison between zinc sheet with Se film and pure zinc sheet; (c) optical bandgap of Se film determined by Tauc Plot method; (d) Raman spectrum of Se film.
[0030] Figure 3 The constant current charge-discharge curves of zinc-iodine button cells constructed using pure zinc sheets and zinc sheets coated with Se as negative electrodes, respectively, combined with activated carbon positive electrodes, are compared.
[0031] Figure 4 These are microscopic images of the zinc anode surface after 50 full cell cycles. (a) Zinc sheet with a Se film on the surface; (b) Pure zinc sheet without surface treatment.
[0032] Figure 5 (a) Dark-field TEM (inset) and EDS elemental analysis of the nanosheet network structure formed on the surface of the zinc anode with a Se film during cycling. (b, c) Low- and high-magnification TEM images of the nanosheet structure.
[0033] Figure 6 (a) A comparison of the cycle performance of full cells constructed using zinc anodes with a Se film on their surface and pure zinc anodes, respectively. The electrolyte was an aqueous solution containing zinc iodide, zinc bromide, zinc sulfate, and elemental iodine. (b) A comparison of the cycle performance of zinc-iodine full cells constructed using these two types of zinc anodes.
[0034] Figure 7 It is a small electric fan driven by two zinc-iodine batteries connected in series.
[0035] Figure 8 This is a flowchart of a method for preparing an aqueous zinc-iodine battery without an ion exchange membrane, provided by the present invention. Detailed Implementation
[0036] Embodiments of the present invention are described in detail below, examples of which are illustrated in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.
[0037] Please see Figures 1 to 8 This invention provides a method for preparing an aqueous zinc-iodine battery without an ion exchange membrane, comprising the following steps:
[0038] S1 Weigh out the selenium source, sodium acetate and organic alcohol according to a certain molar ratio, add deionized water and stir to dissolve to obtain the reaction solution;
[0039] Specifically, the selenium source is one or more of selenium dioxide, selenite, sodium selenite, and sodium biselenite, with sodium acetate added to adjust the pH to 4.5-5.5; the concentration of selenium in the selenium source is 0.1-0.5 M; the organic alcohol is one or more of ethanol, ethylene glycol, isopropanol, and glycerol, with a volume fraction of 5%-30%; and the concentration of sodium acetate is 0.02-0.05 M.
[0040] S2 The cleaned zinc sheet is immersed in the reaction solution for deposition reaction. The zinc sheet after reaction is washed with deionized water and anhydrous ethanol in sequence. After vacuum drying, a zinc anode with a selenium-rich amorphous Se nanofilm on the surface is obtained, denoted as Zn@Se.
[0041] Specifically, the soaking is carried out at room temperature and normal pressure for 1-12 hours; the cleaning process includes ultrasonic cleaning of the zinc sheet with an organic solvent, rinsing with deionized water, and then drying; the organic solvent is a mixture of acetone and ethanol. The deposition reaction takes 0.5-2 hours.
[0042] S3 uses the Zn@Se as the negative electrode, the activated carbon coating or self-supporting film as the positive electrode, and an aqueous solution containing zinc sulfate, zinc iodide, zinc bromide and iodine as the electrolyte to construct a zinc-iodine rechargeable battery.
[0043] Specifically, during the deposition / stripping cycle of zinc sheets coated with amorphous Se in an electrolyte containing zinc iodide, an amorphous zinc hydroxide / zinc oxide nanosheet network structure can be induced to grow in situ, which plays an important role in suppressing the shuttle effect of hydrogen evolution and iodide ions.
[0044] The method for preparing the activated carbon coating includes:
[0045] S31 conductive carbon cloth or carbon paper is ultrasonically cleaned in 1 M dilute nitric acid for 3 hours, then repeatedly cleaned with deionized water until neutral; after drying in a 60℃ oven for 6 hours, hydrophilic carbon cloth or hydrophilic carbon paper is obtained.
[0046] S32 porous activated carbon powder, polyvinylidene fluoride, and acetylene black were dispersed in N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1, and then magnetically stirred for 12 hours to obtain a carbon powder slurry with a concentration of 20 mg / mL.
[0047] S33 The carbon powder slurry is uniformly coated onto the hydrophilic carbon cloth or hydrophilic carbon paper, and then dried in an oven at 100°C for 12 hours to obtain an activated carbon coating.
[0048] Specifically, the mass loading of the activated carbon coating can be controlled between 2-10 mg / cm³. 2 between.
[0049] Beneficial effects:
[0050] (1) The present invention uses a simple chemical bath deposition method to modify zinc sheets.
[0051] (2) Surface-modified Zn anodes show excellent effects in improving coulombic efficiency, corrosion resistance, inhibiting hydrogen evolution and extending charge-discharge cycle life.
[0052] (3) This method is suitable for normal temperature and pressure conditions, does not require expensive equipment, is easy to scale up, and can process several large zinc sheets at the same time.
[0053] (4) After the zinc sheet is surface modified by the method described in this invention, it can be used not only in aqueous zinc-iodine batteries, but also in rechargeable zinc-ion battery systems with MnO2, V2O5, Prussian blue analogues and aromatic polymers as positive electrode materials.
[0054] Example 1
[0055] (1) An aqueous zinc-iodine battery without an ion exchange membrane and its preparation method, wherein the negative electrode is mainly made of commercial zinc sheet / foil as raw material, which is cut into a rectangle and ultrasonically cleaned in a mixed solution of acetone and anhydrous ethanol for 10-30 minutes, and then cleaned with deionized water.
[0056] (2) Prepare the reaction solution: Weigh 0.8 g of selenium dioxide and 0.5 g of sodium acetate, and dissolve them in a mixture of 100 mL of deionized water and 20 mL of glycerol.
[0057] (3) The cleaned zinc sheet was immersed in the above reaction solution and reacted at room temperature for 2 hours to obtain a zinc sheet with a brown film on its surface. Its macroscopic and microscopic morphologies are as follows: Figure 1As shown in (a) and (b), X-ray photoelectron spectroscopy (XPS) analysis confirmed the presence of Se, as shown in... Figure 2 As shown in (a). However, the elemental content of Se and Zn is much higher than 1, approximately 12, so the main component of the film is elemental Se. X-ray diffraction (XRD) analysis revealed that the diffraction peaks of the zinc sheet with the Se film on its surface are consistent with those of the pure zinc sheet, indicating that the formed Se film has an amorphous structure, as shown in (a). Figure 2 As shown in (b), using the Tauc Plot method, the band gap of the Se film was found to be 1.86 eV based on UV-Vis spectroscopy, which is quite close to the band gap of crystalline Se (1.85 eV). Figure 2 As shown in (c), Raman scattering spectroscopy results indicate that the film exhibits the same characteristic peaks as Se, such as... Figure 2 As shown in (d), it is therefore inferred that the Se film is mainly composed of amorphous Se.
[0058] (4) Two identical circular discs were punched from the zinc sheet with Se on its surface and the pure zinc sheet from step (3). Using a glass fiber separator, an aqueous electrolyte containing 1 M zinc sulfate, 0.5 M zinc iodide, and 0.1 M zinc bromide, and a conductive carbon cloth positive electrode coated with activated carbon (AC), CR2032 button batteries were assembled and subjected to a constant current charge-discharge test at 0.1 A / g. The results are as follows: Figure 3 As shown, the median discharge plateau voltage is ~1.2V, indicating that the full cell prepared with a surface-modified Se zinc anode has a significantly higher capacity than the cell using a pure zinc sheet.
[0059] After 50 cycles of constant current charge-discharge, the button cell casing was disassembled, and the negative electrode was removed for scanning electron microscopy. It was found that the zinc sheet covered with a Se film exhibited an amorphous nanosheet network structure induced by the Se on its surface. Figure 4 As shown in (a). However, a pure zinc sheet negative electrode will generate ZnO crystal particles as a byproduct, such as... Figure 4 As shown in (b). For the nanosheet network structure, transmission electron microscopy (TEM) observation of individual nanosheets revealed that the nanosheets had rough surfaces and were relatively thin, such as... Figure 5 As shown in (a). Analysis of the high-resolution transmission electron microscopy (HTEM) image reveals no obvious crystalline surface striations in the nanosheet, indicating that it has an amorphous structure. Figure 5 As shown in (b). Energy dispersive spectroscopy (EDS) analysis revealed the absence of Se in the nanosheets, and the Zn to O ratio was approximately 1:2. Figure 5 As shown in (c), it is therefore speculated that the nanosheet is a two-dimensional nanostructure of amorphous Zn(OH)2 and ZnO.
[0060] (5) Construct a symmetrical battery by combining the Se-coated zinc sheet with a pure zinc sheet, and perform a cycle test using the electrolyte from step (4). The results are as follows: Figure 6 As shown in (a). The coin cell prepared in step (4) was subjected to long-cycle testing, and the results were... Figure 6 As shown in (b), whether it is a symmetrical cell or a full cell, the device using a Se-covered zinc anode exhibits a significantly longer cycle life than the device using a pure zinc anode. This is attributed to the ion conduction properties of Se and the amorphous Zn(OH)₂ and ZnO composite nanosheet network structure it induces, which has functions such as suppressing hydrogen evolution and dendrite formation, and suppressing the shuttle effect of iodine ions. In particular, for the full cell, the cell using a Se-covered zinc anode retains 89% of its capacity after 30,000 cycles, while the full cell using a pure zinc anode fails after only about 10,000 cycles, with a final capacity retention of 74%.
[0061] (6) In addition to the button cell as described in step (3), the zinc sheet negative electrode with an amorphous Se film covering its surface in this invention can also be combined with an activated carbon positive electrode, a separator, and the iodine-containing electrolyte as described in step (3) to form a box-type zinc-iodine battery. Figure 7 As shown, two zinc-iodine batteries based on a plastic casing are connected in series to drive a small electric fan. Therefore, the surface Se-modified zinc anode and the electrolyte in this invention can be used in small button-type and large box-type zinc-iodine batteries, eliminating the need for the ion exchange membrane used in conventional zinc-iodine flow batteries.
[0062] Table 1 shows a comparison of Examples 1-8. Except for the different solution composition used to prepare Se, Examples 1-8 are identical to Example 1.
[0063] Table 1. Solution ratios for growing Se films on zinc sheet surfaces in different examples.
[0064] 1 <![CDATA[SeO2, 0.2 mol / L]]> 0.01 mol / L Ethanol, 10% 1 2 <![CDATA[SeO2, 0.05 mol / L]]> 0.02 mol / L Ethanol, 25% 2 3 <![CDATA[Na2SeO3, 0.1 mol / L]]> 0.01 mol / L Ethylene glycol, 15% 3 4 <![CDATA[Na2SeO3, 0.2 mol / L]]> 0.05 mol / L Glycerol, 20% 4 5 <![CDATA[H2SeO3, 0.1 mol / L]]> 0.03 mol / L Isopropanol, 15% 3 6 <![CDATA[H2SeO3, 0.05 mol / L]]> 0.02 mol / L Ethylene glycol, 25% 2 7 <![CDATA[NaHSeO3, 0.1 mol / L]]> 0.02 mol / L Ethanol, 25% 3 8 <![CDATA[NaHSeO3, 0.05 mol / L]]> 0.05 mol / L Isopropanol, 20% 1
[0065] Secondly, the present invention provides an aqueous zinc-iodine battery without an ion exchange membrane, comprising a negative electrode, a positive electrode, and an electrolyte;
[0066] The negative electrode is Zn@Se ;
[0067] The positive electrode is an activated carbon coating or a self-supporting membrane;
[0068] The electrolyte is an aqueous solution containing zinc sulfate, zinc iodide, zinc bromide and elemental iodine.
[0069] Conclusion: All the above embodiments of the present invention can generate an amorphous Se nano-coating layer on the surface of the zinc sheet, resulting in a surface-modified zinc anode that can be used in aqueous zinc-iodine rechargeable batteries. The specific process is summarized as follows: Figure 8The amorphous Se coating can induce the formation of an amorphous Zn(OH)2 / ZnO mixed nanosheet network structure during the cycling process of the zinc anode, thereby inhibiting the corrosion of the zinc anode and the generation of zinc dendrites and hydrogen evolution during cycling, and greatly improving the cycle life of aqueous zinc-iodine rechargeable batteries.
[0070] The above-disclosed method is merely a preferred embodiment of the preparation method of an aqueous zinc-iodine battery without an ion exchange membrane according to the present invention. Of course, it should not be construed as limiting the scope of the present invention. Those skilled in the art can understand that all or part of the process of the above-described embodiments can be implemented, and equivalent changes made in accordance with the claims of the present invention are still within the scope of the invention.
Claims
1. A method for preparing an aqueous zinc-iodine battery without an ion exchange membrane, characterized in that, Includes the following steps: (1) Weigh out the selenium source, sodium acetate, and organic alcohol according to a certain molar ratio, add deionized water and stir to dissolve to obtain a reaction solution; the selenium source in the reaction solution is one of selenium dioxide, selenite, sodium selenite and sodium biselenite, and sodium acetate is added to adjust the pH value to 4.5-5.5; the organic alcohol is one or more of ethanol, ethylene glycol, isopropanol and glycerol; (2) The zinc sheet after cleaning is immersed in the reaction solution for chemical bath deposition reaction. The zinc sheet after reaction is washed with deionized water and anhydrous ethanol in sequence. After vacuum drying, a zinc anode with an amorphous Se nanofilm on the surface is obtained, denoted as Zn@Se. (3) Using Zn@Se as the negative electrode, activated carbon coating as the positive electrode, and an aqueous solution containing zinc sulfate, zinc iodide, zinc bromide and iodine as the electrolyte, a zinc-iodine rechargeable battery is constructed.
2. The method for preparing an aqueous zinc-iodine battery without an ion exchange membrane as described in claim 1, characterized in that, The concentration of selenium in the selenium source is 0.1 - 0.5 M; The concentration of the sodium acetate is 0.02 - 0.05 M; The volume fraction of the organic alcohol is 5% - 30%.
3. The method for preparing an aqueous zinc-iodine battery without an ion exchange membrane as described in claim 1, characterized in that, The soaking was carried out at room temperature and normal pressure for 1-12 hours; The deposition reaction takes 0.5 to 2 hours.
4. The method for preparing an aqueous zinc-iodine battery without an ion exchange membrane as described in claim 1, characterized in that, The method for preparing the activated carbon coating includes: Conductive carbon fiber cloth, carbon fiber paper, or graphite fiber felt are used as current collectors. They are ultrasonically cleaned in 1 M dilute nitric acid for 3 hours, and then repeatedly cleaned with deionized water until neutral. After drying in an oven at 60°C for 6 hours, a hydrophilic carbon-based current collector is obtained. Porous activated carbon powder, polyvinylidene fluoride, and acetylene black were dispersed in N-methylpyrrolidone at a mass ratio of 8:1:1, and then magnetically stirred for 12 hours to obtain a carbon powder slurry with a concentration of 20 mg / mL. The carbon powder slurry is uniformly coated onto the carbon-based current collector, and then dried in an oven at 100 °C for 12 hours to obtain an activated carbon coated positive electrode.
5. The aqueous zinc-iodine battery without an ion exchange membrane as described in claim 1, characterized in that, Includes the negative electrode, positive electrode, and electrolyte; The negative electrode is Zn@Se; The positive electrode is an activated carbon coating; The electrolyte is an aqueous solution containing zinc sulfate, zinc iodide, zinc bromide and elemental iodine.
Citation Information
Patent Citations
A zinc-iodine flow battery
CN105742656B
Surface treatment method for improving performance of zinc negative electrode and application
CN114335447A
Zinc negative electrode active material
JP1993144431A